Desain Pengembangan Pariwisata dan Ekonomi Masyarakat di Pantai Botutonuo - Febiola Kusuma; Muhammad Amir Arham; Sri Indriyani S. Dai (Universitas Negeri Gorontalo, 2020)
The research aims to find out the Design of Development of Tourism and community Economic in Botutonuo Beach, Bone Bolango District by distributing questionnaire to respondents. The data are collected from result of observation, questionnaire, and documentation. The data analysis user SWOT analysis to discover the IFAS and EFAS, SWOT matrix, and strategy diagram in the SWOT. The research finding shows that the position of development strategy of tourism and community economic in Botutonuo Beach, Bone Bolango District is currently in quadrant III or Turnaround strategy. The strategy emphasizes the importance of government commitment on focus of regional tourism development which can be performed through (1) implementing sapta pesona (seven ways of enchantment) for Botutonuo Beach as tourist attraction, (2) creating city branding for Botutonuo Beach, (3) conducting capacity building for neighboring community in terms of community-based creative economy and tourism, (4) creatimg tourism master plan and sustainable development, (5) optimizing role of tourism institution in meeting Locally-Generated Revenue target of the District and improving community economic including in reducing poverty and increasing labor absorption in Botutonuo Village. The development strategy should be encouraged more and directed properly to improve the tourism comparative and competitive advantages in Bone Bolango District.